Quantum dot light-emitting device and preparation method thereof, and display device
By adopting the electron transport layer structure of ZnTiO3 and Alq3 stacked in the quantum dot light emitting diode, the problem of electron and hole injection is solved, the device efficiency is improved and the life span is extended.
Patent Information
- Application Number
- CN202210262011.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-16
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-03-16
AI Technical Summary
In the existing quantum dot light emitting diode (QLED) devices, the injection of electrons and holes is unbalanced, resulting in limited efficiency improvement, and the stability of the electron transport layer material ZnO is poor, which easily leads to fluorescence quenching of quantum dots.
The first sub-electron transport layer of ZnTiO3 and the second sub-electron transport layer of Alq3 are adopted to increase the electron injection barrier, slow down the electron injection rate, and balance the injection and transmission of electrons and holes.
It effectively improves the efficiency of quantum dot light emitting devices, extends the service life of the device, and reduces the fluorescence quenching of quantum dots.
Smart Images

Figure CN114725294B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of quantum dot technology, and in particular to a quantum dot light-emitting device and a preparation method thereof, and a display device. Background Art
[0002] Quantum dots have been widely used in light-emitting diodes, solar cells, biological imaging, detectors and many other fields. Among them, quantum dot light-emitting diodes (QLEDs) have become a favorable competitor for the next generation of display technology due to their many advantages such as high color purity, adjustable light color, and good stability. However, most of the current research on QLEDs is still in the experimental stage, and the main reason for limiting the pace of QLED industrialization is the efficiency and life of QLED devices.
[0003] Since the hole mobility in current QLED devices is smaller than the electron mobility, the injection and transmission efficiency of electrons in the device is much greater than that of holes, resulting in an unbalanced injection of electrons and holes, which limits the improvement of device efficiency. In addition, the commonly used electron transport layer material in QLED devices is zinc oxide (ZnO), and ZnO has relatively many surface defect states. The ZnO electron transport layer is in direct contact with the quantum dot layer, which can easily cause fluorescence quenching of the quantum dots. In addition, a single ZnO is extremely unstable in the air and is prone to agglomeration.
[0004] Therefore, the current quantum dot light-emitting devices and their preparation methods still need to be improved. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0006] In one aspect of the present invention, the present invention proposes a quantum dot light-emitting device, which includes: an anode; a quantum dot layer, the quantum dot layer is arranged on one side of the anode; an electron transport layer, the electron transport layer is arranged on the side of the quantum dot layer away from the anode, the electron transport layer includes a first sub-electron transport layer and a second sub-electron transport layer arranged in a stacked manner, and the first sub-electron transport layer is arranged close to the quantum dot layer; a cathode, the cathode is arranged on the side of the electron transport layer away from the anode, wherein the material of the first sub-electron transport layer includes ZnTiO3, and the material of the second sub-electron transport layer includes Alq3. Thus, the first sub-electron transport layer and the second sub-electron transport layer can increase the electron injection barrier, slow down the electron injection rate, and then effectively improve the problem that the electron injection and transmission rate is much greater than the hole injection and transmission rate, balance the injection and transmission of electrons and holes, and thus improve the efficiency of the device.
[0007] According to an embodiment of the present invention, the quantum dot light-emitting device further comprises: a hole injection layer, which is arranged between the anode and the quantum dot layer; and a hole transport layer, which is arranged between the hole injection layer and the quantum dot layer.
[0008] According to an embodiment of the present invention, the material of the hole injection layer includes at least one of PEDOT:PSS, PTPDES, PTPDES:TPBAH, PFO-co-NEPBN, PFO-co-NEPBN:F4-TCNQ, molybdenum oxide, tungsten oxide, NiO, and CuO.
[0009] According to an embodiment of the present invention, the material of the hole transport layer includes at least one of TFB, PVK, TCTA, TPD, polyTPD, and CBP.
[0010] According to an embodiment of the present invention, the material of the quantum dot layer includes at least one of a II-VI compound, a III-V compound, a II-V compound, a III-VI compound, a IV-VI compound, a I-III-VI compound, a II-IV-VI compound or a IV element.
[0011] According to an embodiment of the present invention, the material of the quantum dot layer includes at least one of an inorganic perovskite semiconductor and an organic-inorganic hybrid perovskite semiconductor.
[0012] According to an embodiment of the present invention, the general structural formula of the inorganic perovskite semiconductor is CsMX3, wherein M is a divalent metal cation and X is a halogen anion; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BNY3, wherein B is an organic amine cation, N is a divalent metal cation, and Y is a halogen anion; optionally, M and N each independently include Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of; Optionally, X and Y each independently include Cl - Br - or I - At least one of .
[0013] In another aspect of the present invention, the present invention proposes a method for preparing the aforementioned quantum dot light-emitting device, the method comprising: forming an anode; coating a quantum dot solution on one side of the anode, heating to obtain a quantum dot layer; forming an electron transport layer on the side of the quantum dot layer away from the anode; evaporating to form a cathode on the side of the electron transport layer away from the anode, wherein forming the electron transport layer comprises: coating an ethylene glycol ether solution of ZnTiO3 on the side of the quantum dot layer away from the anode, and heating to obtain a first sub-electron transport layer; coating an ethanol solution of Alq3 on the surface of the first sub-electron transport layer away from the anode, and heating to obtain a second sub-electron transport layer. The hole injection and transmission efficiency of the quantum dot light-emitting device prepared by this method matches the electron injection and transmission efficiency, achieving a better balance state, which can effectively improve the efficiency of the quantum dot light-emitting device and extend the service life of the quantum dot light-emitting device.
[0014] According to an embodiment of the present invention, the preparation method of the ethylene glycol ether solution of ZnTiO3 includes: using ZnCl2 and TiCl4 as raw materials, ammonia water as a mineralizer, and deionized water as a medium in a reactor, and reacting ZnCl2, TiCl4 and ammonia water in the reactor at 270-290 degrees for 8h-10h; then subjecting the reaction product in the reactor to high-temperature annealing treatment to obtain ZnTiO3; finally, preparing the ZnTiO3 ethylene glycol ether solution, optionally, the temperature of the high-temperature annealing treatment is 800-900°C.
[0015] According to an embodiment of the present invention, the method further includes: coating a hole injection layer coating liquid on the surface of the anode and performing heat treatment to obtain the hole injection layer; coating a hole transport layer coating liquid on the surface of the hole injection layer away from the anode and performing heat treatment to obtain the hole transport layer.
[0016] In another aspect of the present invention, the present invention provides a display device, which includes the quantum dot light-emitting device described above. Therefore, the display device has all the features and advantages of the quantum dot light-emitting device described above, which will not be repeated here. In general, the display device has a good display effect and a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A schematic diagram of the structure of a quantum dot light-emitting device according to an embodiment of the present invention is shown;
[0018] Figure 2 A schematic diagram showing the structure of a quantum dot light-emitting device according to another embodiment of the present invention is shown;
[0019] Figure 3A film forming effect diagram of the quantum dot light-emitting device of Example 1 is shown;
[0020] Figure 4 The film forming effect diagram of the quantum dot light-emitting device of Comparative Example 1 is shown;
[0021] Figure 5 A film forming effect diagram of the quantum dot light emitting device of Example 2 is shown;
[0022] Figure 6 The film forming effect diagram of the quantum dot light-emitting device of Comparative Example 2 is shown. DETAILED DESCRIPTION
[0023] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0024] In one aspect of the present invention, the present invention provides a quantum dot light emitting device, referring to Figure 1 The quantum dot light emitting device comprises an anode 100, a quantum dot layer 200, an electron transport layer 300 and a cathode 400. Specifically, refer to Figure 1 , the quantum dot layer 200 is arranged on one side of the anode 100, the electron transport layer 300 is arranged on the side of the quantum dot layer 200 away from the anode, and the electron transport layer 300 includes a first sub-electron transport layer 310 and a second sub-electron transport layer 320 which are stacked, the first sub-electron transport layer 310 is arranged close to the quantum dot layer 200, and the cathode 400 is arranged on the side of the electron transport layer 300 away from the anode, wherein the material of the first sub-electron transport layer 310 includes ZnTiO3, and the material of the second sub-electron transport layer includes Alq3. Thus, the first sub-electron transport layer and the second sub-electron transport layer can increase the electron injection barrier, slow down the electron injection rate, and effectively improve the problem that the electron injection and transmission rate is much greater than the hole injection and transmission rate, and can balance the injection and transmission of electrons and holes, thereby improving the efficiency (including external quantum efficiency) of the quantum dot light-emitting device; and can reduce the fluorescence quenching of quantum dots, improve the overall performance of quantum dot light-emitting devices; and can also extend the service life of quantum dot light-emitting devices.
[0025] The following is an explanation of the principle by which the technical solution of the present invention can achieve the above-mentioned effects: the commonly used electron transport layer material is ZnO, and there are many surface defect states of ZnO, which will cause fluorescence quenching of the quantum dots when in direct contact with the quantum dot layer. Specifically, there are a large number of ligands on the surface of quantum dots, such as carboxyl, hydroxyl, amino, etc. When these groups combine with the surface groups of metal ions, they will form complexes that are adsorbed on the surface of quantum dots, causing the quantum dots to agglomerate and increase the particle size, resulting in fluorescence quenching; and, single ZnO is extremely unstable in the air and is prone to agglomeration, which in turn causes quality problems such as uneven film layers and the presence of black spots. The inventors found that TiO2 has good stability in the air and has a slower electron mobility than ZnO, while ZnTiO3 has an electron mobility between TiO2 and ZnO, a moderate electron mobility, and better stability than ZnO, making it an ideal electron transport layer material; aluminum can be used as a cathode in quantum dot light-emitting devices, and the barrier difference between tri(8-hydroxyquinoline)aluminum (Alq3) and the aluminum electrode (the barrier difference between Alq3 and aluminum is 1.2 eV) is larger than that between ZnTiO3 (the barrier difference between Alq3 and aluminum is 0.4 eV), and stacking ZnTiO3 and Alq3 as an electron transport layer can increase the electron injection barrier, slow down the electron injection rate, and balance the injection and transmission of electrons and holes. At the same time, ZnTiO3 can also improve the fluorescence quenching of quantum dots, so that the device has better performance, and can also effectively extend the service life of the device.
[0026] According to an embodiment of the present invention, the material of the anode 100 may include ITO (indium tin oxide), IZO (indium zinc oxide), etc. Therefore, the above materials have good electrical conductivity, which is conducive to improving the overall performance of the quantum dot light-emitting device.
[0027] According to some embodiments of the present invention, the material of the quantum dot layer 200 may include at least one of a II-VI compound, a III-V compound, a II-V compound, a III-VI compound, a IV-VI compound, a I-III-VI compound, a II-IV-VI compound, or a IV simple substance. Thus, the quantum dot layer can emit light under the excitation of holes and electrons. According to some specific embodiments of the present invention, the material of the quantum dot layer 200 may include, but is not limited to, one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, PbS, PbSe, PbTe, GaP, GaAs, InP, InAs, and other binary, ternary, and quaternary compounds.
[0028] According to other embodiments of the present invention, the material of the quantum dot layer 200 may include at least one of an inorganic perovskite semiconductor and an organic-inorganic hybrid perovskite semiconductor. Thus, the quantum dot layer formed by the above materials can also emit light under the excitation of holes and electrons.
[0029] According to some embodiments of the present invention, the general structural formula of the inorganic perovskite semiconductor is CsMX3, wherein M is a divalent metal cation and X is a halogen anion. According to some specific embodiments of the present invention, M may include Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X may include Cl - Br - or I - At least one of .
[0030] According to some embodiments of the present invention, the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BNY3, wherein B is an organic amine cation, N is a divalent metal cation, and Y is a halogen anion. According to some specific embodiments of the present invention, N may include Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, Y may include Cl - Br - or I - According to some other specific embodiments of the present invention, the organic amine cation can be selected from but not limited to CH3(CH2) n -2NH3 + (n≥2) or NH3(CH2) n NH3 2+ (n≥2); when n=2, the inorganic metal halide octahedron MX6 4-The metal cation M is located at the center of the halogen octahedron, and the organic amine cation B fills the gap between the octahedrons to form an infinitely extended three-dimensional structure. When n>2, the inorganic metal halide octahedron MX6 connected by the top-sharing method 4- It extends in two dimensions to form a layered structure, with an organic amine cation bilayer (protonated monoamine) or an organic amine cation monolayer (protonated diamine) inserted between the layers, and the organic layer and the inorganic layer overlap to form a stable two-dimensional layered structure.
[0031] According to an embodiment of the present invention, the material of the cathode 400 includes aluminum, so that the cathode has good electrical conductivity, which is beneficial to improving the performance of the quantum dot light-emitting device.
[0032] According to some embodiments of the present invention, reference Figure 2 The quantum dot light emitting device may further include: a hole injection layer 500 and a hole transport layer 600, wherein the hole injection layer 500 is disposed between the anode 100 and the quantum dot layer 200, and the hole transport layer 600 is disposed between the hole injection layer 500 and the quantum dot layer 200. Thus, the overall performance of the quantum dot light emitting device can be further improved.
[0033] According to some embodiments of the present invention, the material of the hole injection layer 500 may include at least one of PEDOT:PSS, PTPDES, PTPDES:TPBAH, PFO-co-NEPBN, PFO-co-NEPBN:F4-TCNQ, molybdenum oxide, tungsten oxide, NiO, and CuO. The hole injection layer 500 is made of the above materials and has a suitable hole injection rate, which can further improve the overall performance of the quantum dot light-emitting device.
[0034] Among them, PEDOT:PSS (poly 3,4-ethylenedioxythiophene: polystyrene sulfonate), PTPDES (tetraphenyldiamine-containing poly arylene ether sulfone, polyarylethersulfone polymer containing tetraphenyldiamine), PTPDES:TPBAH (PTPDES:TPBAH is a P-doped composition of PTPDES, TPBAH (tris(4-bromophenyl)aminium hexachloroantimonate, 3(4-bromophenyl)ammonium hexachloroantimonate, is an electron acceptor of bromophenyl salts and can be P-doped)), PFO-co-NEPBN (poly(9,9-dioctylfluorene-co-bis-N,N-(4-ethoxycarbonylphenyl)-bis-N,N-phenylbenzidine, poly(9,9-dioctylfluorene-co-bis-N,N-(4-ethoxycarbonylphenyl)-bis-N,N-phenylbenzidine)), PFO-co-NEPBN:F4-TCNQ (is a P-doped composition of PFO-co-NEPBN, F4-TCNQ (2,3,5,6-Tetrafluoro-7,7,8,8-tetracyanoquinodimethane, 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane, is a small molecule P-type dopant and can be P-doped)).
[0035] According to an embodiment of the present invention, the material of the hole transport layer 600 may include at least one of TFB, PVK, TCTA, TPD, polyTPD, and CBP. As a result, the hole transport layer has a suitable hole transport rate, which is beneficial to further improve the overall performance of the quantum dot light-emitting device. Among them, TFB refers to 1,2,4,5-tetrakis (trifluoromethyl) benzene, PVK refers to polyvinyl carbazole, TCTA refers to 4,4,4,-tris (carbazole-9-yl) triphenylamine, TPD refers to N,N'-diphenyl-N,N'-di (3-methylphenyl) -1,1'-biphenyl-4,4'-diamine, polyTPD (Poly: TPD) is a polymer of TPD, and CBP refers to 4,4'-di (9-carbazole) biphenyl.
[0036] In addition, according to some other embodiments of the present invention, Figure 2 The quantum dot light-emitting device may further include a substrate 700, wherein the substrate 700 is disposed on a side of the anode 100 away from the quantum dot layer 200. The substrate 700 may be made of glass, so that the substrate can provide good support for the anode, the quantum dot layer, the electron transport layer, the cathode, etc., thereby improving the stability of the quantum dot light-emitting device.
[0037] In general, the quantum dot light-emitting device proposed in the present invention adopts a stacked ZnTiO3 first sub-electron transport layer and an Alq3 second sub-electron transport layer, which can increase the electron injection barrier, slow down the rate of electron injection and transmission, and thus balance the injection and transmission of electrons and holes, and can improve the fluorescence quenching of quantum dots, thereby effectively improving the efficiency of the quantum dot light-emitting device and extending the service life of the quantum dot light-emitting device.
[0038] In another aspect of the present invention, the present invention provides a method for preparing the aforementioned quantum dot light-emitting device, the method comprising:
[0039] S100: forming an anode 100.
[0040] First, the anode 100 is formed. According to some specific embodiments of the present invention, the anode 100 can be formed on a surface of a substrate 700. The substrate 700 can be made of glass. The glass substrate 700 can provide good support for the quantum dot light-emitting device, and the glass surface is smooth, which is conducive to the subsequent evaporation or coating of the functional film layer.
[0041] According to some other specific embodiments of the present invention, before forming the anode 100 , the substrate 700 may be cleaned to facilitate the subsequent formation of an anode on the surface of the substrate.
[0042] According to some embodiments of the present invention, the anode 100 may be patterned, that is, the anode 100 may include a plurality of sub-anodes, and a plurality of sub-light emitting structures may be formed, and each sub-light emitting structure may be individually controlled by its own sub-anode.
[0043] In addition, the specific method for forming the anode is not particularly limited in the present invention, as long as a flat anode structure can be formed on the surface of the substrate. The specific material of the anode has been introduced above and will not be repeated here.
[0044] S200: coating a quantum dot solution on one side of the anode and performing a heat treatment to obtain a quantum dot layer 200 .
[0045] After forming the anode 100, a quantum dot solution is coated on one side of the anode 100, and then a heat treatment is performed to obtain the quantum dot layer 200. The material of the quantum dot layer 200 has been described in detail above and will not be repeated here.
[0046] According to some embodiments of the present invention, the quantum dot solution can be first filtered using a filter head (e.g., a filter head with a pore size of 0.25 μm) to obtain a quantum dot particle size not exceeding 0.25 microns. The quantum dot solution is coated on one side of the anode 100 and then heat treated to obtain a quantum dot layer 200. According to some specific embodiments of the present invention, the quantum dot solution can be coated by spin coating, and the spin coating rate can be 2000rpm-5000rpm, for example, 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm, 4500rpm, 5000rpm, etc., and the spin coating time can be 20s-40s, for example, 20s, 25s, 30s, 35s, 40s, etc., thereby, a uniform and flat quantum dot coating layer can be formed; thereafter, the quantum dot coating layer is subjected to a heat treatment (for example, an annealing treatment), and the heating temperature can be 55°C-65°C, for example, 55°C, 58°C, 60°C, 63°C, 65°C, etc., and the heating time can be 4min-6min, for example, 4min, 5min, 6min, etc., thereby, the solvent or volatile substance in the quantum dot coating layer can be removed to obtain a flat and uniform quantum dot layer.
[0047] In addition, according to some other embodiments of the present invention, before forming the quantum dot layer 200, a hole injection layer 500 may be formed on the surface of the anode 100 away from the substrate 700. According to some embodiments of the present invention, the step of forming the hole injection layer includes: coating a hole injection layer coating liquid on the surface of the anode 100 (on the surface away from the substrate 700), and performing a heat treatment to obtain the hole injection layer 500. The material of the hole injection layer 500 has been described in detail above and will not be repeated here.
[0048] According to some specific embodiments of the present invention, a hole injection layer aqueous solution is filtered using a filter head (e.g., a filter head with a pore size of 0.45 um) to obtain a hole injection layer coating liquid, wherein the filtration can remove larger particles of the hole injection layer particles, and then the hole injection layer coating liquid is coated on the surface of the anode 100, followed by a heat treatment to obtain the hole injection layer 500. According to some specific embodiments of the present invention, when coating the hole injection layer coating liquid, spin coating can be performed, and the spin coating rate can be 2500rpm-3500rpm, for example, 2500rpm, 2800rpm, 3000rpm, 3200rpm, 3500rpm, etc., and the spin coating time can be 20s-40s, for example, 20s, 25s, 30s, 35s, 40s, etc., thereby, a uniform and flat hole injection layer coating layer can be formed in a relatively short time using a suitable rotation speed. ; After the hole injection layer coating layer is formed, the coating layer is heated (for example, annealing treatment). According to other specific embodiments of the present invention, the heating temperature can be 130°C-150°C, for example, 130°C, 135°C, 140°C, 145°C, 150°C, etc., and the heating time can be 20min-40min, for example, 20min, 25min, 30min, 35min, 40min, etc., thereby, the solvent or volatile substance in the hole injection layer coating layer can be removed to obtain the hole injection layer.
[0049] According to some embodiments of the present invention, before forming the hole injection layer 500, the substrate 700 formed with the anode 100 may be cleaned. The specific cleaning steps include:
[0050] The substrate formed with the anode is ultrasonically cleaned with glass detergent, deionized water, acetone, and isopropanol in sequence, and then subjected to ultraviolet ozone treatment after drying. Among them, the drying method can be blown dry with a nitrogen gun, which does not require heating and will not cause adverse effects on the substrate or the anode. The substrate formed with the anode is ultrasonically cleaned with different cleaning materials in sequence, and impurities (including organic matter, etc.) on the surface of the substrate or the anode can be removed, and ultraviolet ozone treatment can further remove residual impurities.
[0051] Furthermore, before forming the quantum dot layer 200, a hole transport layer 600 may be formed on the surface of the hole injection layer 500. According to some embodiments of the present invention, a hole transport layer coating liquid may be coated on the surface of the hole injection layer 500 away from the anode 100, and heat treated to obtain the hole transport layer 600. The material of the hole transport layer 600 has been described in detail above and will not be repeated here.
[0052] According to some embodiments of the present invention, after the hole injection layer 500 is formed, the sample is transferred to a glove box, and the prepared hole transport layer coating liquid is coated on the surface of the hole injection layer 500 away from the anode 100, followed by heat treatment to obtain the hole transport layer 600. According to some specific embodiments of the present invention, the hole transport layer coating liquid can be coated by spin coating. In this step, the spin coating rate can be 1500rpm-2500rpm. Specifically, the spin coating rate can be 1500rpm, 1800rpm, 2000rpm, 2300rpm, 2500rpm, etc., and the spin coating time can be 35s-55s, such as 35s, 38s, 40s, 45s, 50s, 55s, etc., thereby, the hole transport layer coating layer can be formed in a shorter time at a suitable rotation speed; after the hole transport layer is formed, the hole transport layer coating layer can be formed in a shorter time at a suitable rotation speed. After the hole transport layer is coated, the coating layer is subjected to a heat treatment (e.g., annealing treatment), the heating temperature may be 100°C-120°C, for example, 100°C, 105°C, 110°C, 115°C, 120°C, etc., the heating time may be 20min-40min, for example, 20min, 23min, 25min, 28min, 30min, 32min, 35min, 38min, 40min, etc., thereby, the solvent or volatile substance in the hole transport layer coating layer may be removed to obtain a smooth hole transport layer 600.
[0053] Those skilled in the art can understand that when a hole injection layer is provided, the quantum dot layer is provided on the side of the hole injection layer away from the anode; when a hole transport layer is provided, the quantum dot layer is provided on the side of the hole transport layer away from the anode.
[0054] S300: forming an electron transport layer 300 on a side of the quantum dot layer away from the anode.
[0055] In this step, the electron transport layer 300 is formed on the side of the quantum dot layer 200 away from the anode 100. According to some embodiments of the present invention, the step of forming the electron transport layer 300 further includes forming a first sub-electron transport layer 310 and forming a second sub-electron transport layer 320.
[0056] According to some embodiments of the present invention, the step of forming the first sub-electron transport layer 310 includes: coating a ZnTiO3 ethylene glycol ether solution on the side of the quantum dot layer 200 away from the anode 100, and performing a heat treatment to obtain the first sub-electron transport layer 310. In this step, the ZnTiO3 ethylene glycol ether solution can be coated by spin coating, and the spin coating rate can be 1500rpm-3500rpm. Specifically, the spin coating rate can be 1500rpm, 1800rpm, 2000rpm, 2300rpm, 2500rpm, 2700rpm, 3000rpm, 3200rpm, 3500rpm, etc., and the spin coating time can be 25s-35s, for example, 25s, 28s, 30s, 32s, 35s, etc., thereby, the ZnTiO3 ethylene glycol ether solution can be coated. The ether solution is uniformly coated on the surface of the quantum dot layer away from the substrate to form a first sub-electron transport layer coating layer; the first sub-electron transport layer coating layer is subjected to a heat treatment (e.g., annealing treatment), the heating temperature can be 55°C-65°C, for example, 55°C, 58°C, 60°C, 63°C, 65°C, etc., the heating time can be 10min-20min, for example, 10min, 12min, 15min, 18min, 20min, etc., thereby, the solvent in the first sub-electron transport layer coating layer can be removed to obtain a uniform and flat first sub-electron transport layer.
[0057] According to some specific embodiments of the present invention, the preparation method of ethylene glycol ether solution of ZnTiO3 includes the following steps: using ZnCl2 and TiCl4 as raw materials, ammonia water as a mineralizer, and deionized water as a medium in the reactor, and reacting ZnCl2, TiCl4 and ammonia water at 270-290 degrees in the reactor for 8h-10h; then the reaction product in the reactor is subjected to high temperature annealing to obtain ZnTiO3; and finally, ZnTiO3 ethylene glycol ether solution is configured. Thus, the formed ZnTiO3 has good performance, can improve the electron injection barrier, and the ZnTiO3 ethylene glycol ether solution configured by it can be well coated on the surface of the quantum dot layer, and the first sub-electron transport layer with excellent performance can be obtained by heating treatment. According to some embodiments of the present invention, the temperature of high temperature annealing treatment of the reaction product in the reactor can be 800-900℃, which is conducive to further improving the performance of the first sub-electron transport layer, and then to improving the performance of the quantum dot device.
[0058] According to some embodiments of the present invention, the step of forming the second sub-electron transport layer 320 includes: coating an ethanol solution of Alq3 on the surface of the first sub-electron transport layer 310 away from the anode 100, and performing a heat treatment to obtain the second sub-electron transport layer 320. According to some specific embodiments of the present invention, the ethanol solution of Alq3 can be coated on the surface of the first sub-electron transport layer 310 away from the anode 100 by spin coating, and the spin coating rate can be 1500rpm-3500rpm. Specifically, the spin coating rate can be 1500rpm, 1800rpm, 2000rpm, 2300rpm, 2500rpm, 2700rpm, 3000rpm, 3200rpm, 3500rpm, etc., and the spin coating time can be 25s-35s, for example, 25s, 28s, 30s, 32s, 35s, etc., thereby , the ethanol solution of Alq3 can be uniformly coated on the surface of the first sub-electron transport layer away from the anode to form a second sub-electron transport layer coating layer; the second sub-electron transport layer coating layer is subjected to a heat treatment (e.g., annealing treatment), the heating temperature can be 75°C-85°C, for example, 75°C, 77°C, 80°C, 82°C, 85°C, etc., the heating time can be 25min-35min, for example, 25min, 27min, 30min, 32min, 35min, etc., thereby, the solvent in the second sub-electron transport layer coating layer can be removed to obtain the second sub-electron transport layer.
[0059] S400 : forming the cathode 400 by evaporation on the side of the electron transport layer 300 away from the anode 100 .
[0060] In this step, the cathode 400 is formed by evaporation on the side of the electron transport layer 300 away from the anode 100. According to some embodiments of the present invention, aluminum can be evaporated on the side of the electron transport layer 300 away from the anode 100 to obtain the cathode 400. Thus, the cathode can be formed using a mature process, which is conducive to improving the yield of the product.
[0061] In general, by using the method proposed in the present invention to prepare quantum dot light-emitting devices, a uniform and flat film layer structure can be formed, and the electron transport layer is formed by stacking a ZnTiO3 first sub-electron transport layer and an Alq3 second sub-electron transport layer, which can increase the electron injection barrier and effectively slow down the electron injection rate, thereby improving the problem that the electron injection and transmission rates are much higher than the hole injection and transmission rates, balancing the injection and transmission of electrons and holes, thereby improving the efficiency of the device and extending the service life of the device.
[0062] In another aspect of the present invention, the present invention provides a display device, which includes the quantum dot light-emitting device described above. Therefore, the display device has all the features and advantages of the quantum dot light-emitting device described above, which will not be repeated here. In general, the display device has a good display effect and a long service life.
[0063] According to the embodiments of the present invention, there are no special requirements for the specific type of the above-mentioned display device, and those skilled in the art can flexibly select it according to actual needs. For example, it can be a mobile phone, iPad, notebook or other display device.
[0064] Those skilled in the art will understand that, in addition to the quantum dot light-emitting device mentioned above, the display device also has the necessary structures and components of a conventional display device. Taking a mobile phone as an example, in addition to the quantum dot light-emitting device mentioned above, it also includes the necessary structures and components such as a battery back cover, a middle frame, a touch panel, an audio module, and a motherboard.
[0065] The present invention is described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer, and are all conventional products that can be obtained commercially.
[0066] Example 1
[0067] Step 1: Form an ITO anode on the surface of a glass substrate, and clean the glass substrate with the ITO anode: place the glass substrate with the ITO anode in glass cleaning agent, deionized water, acetone, and isopropanol for ultrasonic cleaning in sequence, then blow dry the surface with a nitrogen gun, and then perform ultraviolet ozone treatment for 5 minutes.
[0068] Step 2: Preparation of hole injection layer: Filter the hole injection layer aqueous solution (i.e., the aqueous solution of PEDOT:PSS (4083)) with a filter head with a pore size of 0.45um to obtain a hole injection layer coating solution, and then spin-coat the hole injection layer coating solution on the surface of the ITO anode away from the glass substrate at a spin coating rate of 3000rpm for 30s, and then heat at 140°C for 30min to form a hole injection layer. The material of the hole injection layer is PEDOT:PSS.
[0069] Step 3: Preparation of hole transport layer: After forming the hole injection layer, the sample is transferred to a glove box, and the prepared hole transport layer chlorobenzene solution (chlorobenzene solution of TFB) is spin-coated on the surface of the hole injection layer away from the substrate at a spin-coating rate of 2000 rpm for 45 seconds, followed by heating at 120°C for 20 minutes to form a hole transport layer. The material of the hole transport layer is TFB.
[0070] Step 4: Preparation of quantum dot layer:
[0071] 1.2 mmol of indium acetate (In(Ac)3), 0.6 mmol of zinc acetate (Zn(Ac)2) and 3.6 mmol of palmitic acid (PA) were placed in a three-necked flask and heated to 150°C. 0.8 mmol of tri(trimethylsilyl)phosphine (TMS)3P) was dissolved in 1 ml of tri-n-octylphosphine (TOP) and poured into the above solution. The temperature was quickly raised to 290°C and reacted for 5 minutes to obtain InP cores.
[0072] The obtained InP was put into 5M Zn(OA)2 solution, heated to 280°C, 1M Se-TOP solution was added dropwise, and reacted for 30 minutes to obtain InP / ZnSe (core-shell structure, with InP as core and ZnSe as shell).
[0073] An InP / ZnSe quantum dot solution was prepared with OCT (n-octane) at a concentration of 20 mg / ml. The quantum dot solution was spin-coated on the surface of the hole transport layer away from the substrate at a spin-coating rate of 2000 rpm for 30 s, and then heated at 60°C for 5 min to form a quantum dot layer.
[0074] Step 5: Preparation of electron transport layer:
[0075] Preparation of the first sub-electron transport layer: ZnTiO3 is synthesized by a hydrothermal method. Specifically, in a reactor, ZnCl2 and TiCl4 are used as raw materials, ammonia water is used as a mineralizer, and deionized water is used as a medium. The reaction is carried out at 270°C for 8 hours, and ZnTiO3 is obtained by annealing at 800°C. The prepared ZnTiO3 is prepared as an ethylene glycol ether solution of ZnTiO3. After the quantum dot layer is formed, the ethylene glycol ether solution of ZnTiO3 is spin-coated on the surface of the quantum dot layer away from the substrate, with a spin-coating rate of 1500rpm and a spin-coating time of 30s, and then heated at 60°C for 15min to obtain the first sub-electron transport layer. Among them, the material of the first sub-electron transport layer is ZnTiO3.
[0076] Preparation of the second sub-electron transport layer: Spin-coat the surface of the first sub-electron transport layer away from the substrate with an ethanol solution of Alq3 at a rate of 1500 rpm for 30 seconds, and then heat at 80°C for 30 minutes to form the second sub-electron transport layer. The material of the second sub-electron transport layer is Alq3.
[0077] Step 6: Preparation of cathode: After forming the second electron transport layer, the sample is transferred to an evaporation coating machine. On the surface of the second electron transport layer away from the substrate, a gas pressure of less than 5×10 -5 An Al electrode (cathode) was formed by evaporation under high vacuum conditions of Pa, thereby preparing device A.
[0078] Comparative Example 1
[0079] The difference from Example 1 is that after the quantum dot layer is formed, an ethanol solution of ZnO is spin-coated on the surface of the quantum dot layer away from the substrate at a spin coating rate of 1500 rpm for 30 seconds, and then heated at 60°C for 15 minutes to obtain an electron transport layer, wherein the material of the electron transport layer is ZnO. After the electron transport layer is formed, the sample is transferred to an evaporation coating machine, and on the surface of the electron transport layer away from the substrate, an ethanol solution of ZnO is spin-coated at a spin coating rate of 1500 rpm for 30 seconds, and then heated at 60°C for 15 minutes to obtain an electron transport layer. -5 An Al electrode (cathode) was formed by evaporation under high vacuum conditions of Pa, thereby preparing device B.
[0080] Comparative Example 2
[0081] The difference from Example 1 is that after the quantum dot layer is formed, an ethanol solution of Alq3 is spin-coated on the surface of the quantum dot layer away from the substrate, the spin coating rate is 1500 rpm, the spin coating time is 30 s, and then heated at 80°C for 30 min to form a first sub-electron transport layer. The material of the first sub-electron transport layer is Alq3. An ethanol solution of zinc oxide is spin-coated on the surface of the first sub-electron transport layer away from the substrate, the spin coating rate is 1500 rpm, the spin coating time is 30 s, and then heated at 80°C for 30 min to form a second sub-electron transport layer. The material of the second sub-electron transport layer is ZnO. After the electron transport layer is formed, the sample is transferred to an evaporation coating machine, and on the surface of the electron transport layer away from the substrate, an evaporation coating machine is used at a pressure of less than 5×10 -5 Pa was evaporated under high vacuum conditions to form an Al electrode (cathode), thereby preparing device B*.
[0082] Example 2
[0083] Step 1: Form an ITO anode on the surface of a glass substrate, and clean the glass substrate with the ITO anode: place the glass substrate with the ITO anode in glass cleaning agent, deionized water, acetone, and isopropanol for ultrasonic cleaning in sequence, then blow dry the surface with a nitrogen gun, and then perform ultraviolet ozone treatment for 5 minutes.
[0084] Step 2: Preparation of hole injection layer: Filter the hole injection layer aqueous solution (i.e., the aqueous solution of PEDOT:PSS (4083)) with a filter head with a pore size of 0.45um to obtain a hole injection layer coating solution, and then spin-coat the hole injection layer coating solution on the surface of the ITO anode away from the glass substrate at a spin coating rate of 3000rpm for 30s, and then heat at 140°C for 30min to form a hole injection layer. The material of the hole injection layer is PEDOT:PSS.
[0085] Step 3: Preparation of hole transport layer: After forming the hole injection layer, the sample is transferred to a glove box, and the prepared hole transport layer chlorobenzene solution (chlorobenzene solution of TFB) is spin-coated on the surface of the hole injection layer away from the substrate at a spin-coating rate of 2000 rpm for 45 seconds, followed by heating at 120°C for 20 minutes to form a hole transport layer. The material of the hole transport layer is TFB.
[0086] Step 4: Preparation of quantum dot layer:
[0087] Preparation of CdSe core:
[0088] 8mmol of cadmium oxide, 8mL of OA (oleic acid), and 72mL of ODE (octadecene) were placed in a three-necked flask, and evacuated with a vacuum pump and then flushed with argon gas. This process was repeated several times to fill the three-necked flask with argon gas, and the temperature was slowly raised to 240°C to allow it to fully react to generate cadmium oleate. The temperature was continued to be raised, and at 280°C, the precursor Se-TOP was quickly injected into the reaction system (cadmium oleate), and then the temperature was continued to be raised to 320°C, and the reaction was continued for 5 minutes to prepare the CdSe core.
[0089] The obtained CdSe core was placed in a 5M Zn(OA)2 solution, heated to 315°C, and 1M S-TOP solution was added dropwise. The reaction was continued for 30 minutes to obtain CdSe / ZnS quantum dots (core-shell structure, with CdSe as core and ZnS as shell).
[0090] A CdSe / ZnS quantum dot solution was prepared with OCT (n-octane) at a concentration of 20 mg / ml, and the quantum dot solution was spin-coated on the surface of the hole transport layer away from the substrate at a spin-coating rate of 2000 rpm for 30 s, followed by heating at 60°C for 5 min to form a quantum dot layer.
[0091] Step 5: Preparation of electron transport layer:
[0092] Preparation of the first sub-electron transport layer: ZnTiO3 is synthesized by a hydrothermal method. In a reactor, ZnCl2 and TiCl4 are used as raw materials, ammonia water is used as a mineralizer, and deionized water is used as a medium. The reaction is carried out at 270°C for 8 hours, and ZnTiO3 is obtained by annealing at 800°C. The prepared ZnTiO3 is prepared as an ethylene glycol ether solution of ZnTiO3. After the quantum dot layer is formed, the ethylene glycol ether solution of ZnTiO3 is spin-coated on the surface of the quantum dot layer away from the substrate, with a spin-coating rate of 1500rpm and a spin-coating time of 30s, and then heated at 60°C for 15min to obtain the first sub-electron transport layer. Among them, the material of the first sub-electron transport layer is ZnTiO3.
[0093] Preparation of the second sub-electron transport layer: Spin-coat the surface of the first sub-electron transport layer away from the substrate with an ethanol solution of Alq3 at a rate of 1500 rpm for 30 seconds, and then heat at 80°C for 30 minutes to form the second sub-electron transport layer. The material of the second sub-electron transport layer is Alq3.
[0094] Step 6: Preparation of cathode: After forming the second electron transport layer, the sample is transferred to an evaporation coating machine. On the surface of the second electron transport layer away from the substrate, a gas pressure of less than 5×10 -5 An Al electrode (cathode) was formed by evaporation under high vacuum conditions of Pa, thereby preparing device C.
[0095] Comparative Example 3
[0096] The difference from Example 2 is that after the quantum dot layer is formed, an ethanol solution of ZnO is spin-coated on the surface of the quantum dot layer away from the substrate at a spin coating rate of 1500 rpm for 30 seconds, and then heated at 60°C for 15 minutes to obtain an electron transport layer, wherein the material of the electron transport layer is ZnO. After the electron transport layer is formed, the sample is transferred to an evaporation coating machine, and on the surface of the electron transport layer away from the substrate, an ethanol solution of ZnO is spin-coated at a spin coating rate of 1500 rpm for 30 seconds, and then heated at 60°C for 15 minutes to obtain an electron transport layer. -5 Pa was evaporated under high vacuum conditions to form Al electrodes, thereby preparing device D.
[0097] The devices in the embodiments and comparative examples were tested to obtain the film quality, lifespan and efficiency (external quantum efficiency) of each device.
[0098] The film quality test steps are as follows: Observe the film quality under an atomic force microscope (AFM).
[0099] The life test method is as follows: the life is tested in the Ocean Optics EQE test system, the time taken for the maximum brightness of the film layer to drop to 95% as the brightness changes over time is taken, and the value obtained by multiplying by the proportionality coefficient is recorded as the device T95 life (i.e. the device life in Table 1).
[0100] External quantum efficiency (EQE): External quantum efficiency is the luminous efficiency of the device, which is the ratio of the number of photons emitted by a quantum dot light-emitting diode device to the number of injected electrons in a certain direction.
[0101] The test results of the efficiency and life of the samples of various embodiments and comparative examples are recorded in Table 1.
[0102] Table 1 Test results of sample efficiency and life of each embodiment and comparative example
[0103] Part Number Device efficiency (EQE, external quantum efficiency) Device life Device A 5%-8% 200h-300h Device B 1%-3% 50h-100h Device B* 2%-4% 100h-150h Device C 12%-16% 150-200h Device D 5%-8% 50-80h
[0104] It should be noted that for each sample, the device efficiency and device life are tested on 10 samples, so the measured values are all range values. As can be seen from Table 1, in both Example 1 and Example 2, a ZnTiO3 first sub-electron transport layer and an Alq3 second sub-electron transport layer are formed. Therefore, the external quantum efficiency of device A and device C is higher and the life span is longer. Compared with device A, device B only uses ZnO as the electron transport layer. Therefore, the external quantum efficiency of device B is significantly lower than that of A, and the life span of device B is also shorter. Compared with device B, device B* uses Alq3 and ZnO as the composite electron transport layer, and the external quantum efficiency and life span of device B* are better than those of device B with a single electron transport layer. Compared with device A, device B* does not form an electron transport layer structure of ZnTiO3 and Alq3 stacked, and its effect on improving the quantum dot injection barrier and improving the fluorescence quenching of quantum dots are not significant enough, resulting in the external quantum efficiency and device life of device B* being lower than those of device A. Compared with device C, device D only uses ZnO as the electron transport layer, and its external quantum efficiency is significantly lower than that of device C, and the life span of the device is also relatively short.
[0105] Figures 3 to 6 The film quality test results of device A, device B, device C and device D are shown respectively. Figure 3 and Figure 5 It can be seen that the film quality of the devices in Example 1 and Example 2 is good, and the film is uniform and flat; Figure 4 and Figure 6 It can be seen that the film quality of the devices in Comparative Examples 1 and 2 is poor, the film formation is uneven, and there are obvious wrinkles and spots (caused by zinc oxide agglomeration).
[0106] From the above experimental results, it can be seen that the ZnTiO3 first electron transport layer and the Alq3 second electron transport layer can significantly improve the film quality of the device, significantly improve the efficiency of the device, and extend the service life of the device.
[0107] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0108] In the description of this specification, the description with reference to the terms "one embodiment", "another embodiment", "some embodiments", "some specific embodiments" or "some other specific embodiments" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0109] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A quantum dot light-emitting device, characterized in that: include: anode; A quantum dot layer, wherein the quantum dot layer is disposed on one side of the anode; An electron transport layer, the electron transport layer is arranged on a side of the quantum dot layer away from the anode, the electron transport layer comprises a first sub-electron transport layer and a second sub-electron transport layer arranged in a stacked manner, and the first sub-electron transport layer is arranged close to the quantum dot layer; a cathode, the cathode being arranged on a side of the electron transport layer away from the anode, the cathode being arranged adjacent to the electron transport layer, The material of the first sub-electron transport layer is ZnTiO3, and the material of the second sub-electron transport layer is Alq3. The cathode is made of aluminum.
2. The quantum dot light-emitting device according to claim 1, characterized in that: Also includes: A hole injection layer, the hole injection layer is disposed between the anode and the quantum dot layer; A hole transport layer is disposed between the hole injection layer and the quantum dot layer.
3. The quantum dot light emitting device according to claim 2, characterized in that: The material of the hole injection layer includes at least one of PEDOT:PSS, PTPDES, PTPDES:TPBAH, PFO-co-NEPBN, PFO-co-NEPBN:F4-TCNQ, molybdenum oxide, tungsten oxide, NiO, and CuO, and the material of the hole transport layer includes at least one of TFB, PVK, TCTA, TPD, polyTPD, and CBP.
4. The quantum dot light-emitting device according to claim 1, characterized in that: The material of the quantum dot layer includes at least one of a II-VI compound, a III-V compound, a II-V compound, a III-VI compound, a IV-VI compound, a I-III-VI compound, a II-IV-VI compound or a IV element.
5. The quantum dot light-emitting device according to claim 1, characterized in that: The material of the quantum dot layer includes at least one of an inorganic perovskite semiconductor and an organic-inorganic hybrid perovskite semiconductor.
6. The quantum dot light emitting device according to claim 5, characterized in that: The inorganic perovskite semiconductor has a general structural formula of CsMX3, wherein M is a divalent metal cation and X is a halogen anion; The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BNY3, wherein B is an organic amine cation, N is a divalent metal cation, and Y is a halogen anion; Optionally, M and N each independently comprise Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of; Optionally, X and Y each independently comprise Cl - Br - or I - At least one of .
7. A method for preparing a quantum dot light-emitting device according to any one of claims 1 to 6, characterized in that: include: forming an anode; Coating a quantum dot solution on one side of the anode and performing a heating treatment to obtain a quantum dot layer; forming an electron transport layer on a side of the quantum dot layer away from the anode; A cathode is formed by evaporating on a side of the electron transport layer away from the anode. Wherein, forming the electron transport layer comprises: Coating a ZnTiO3 ethylene glycol ether solution on the side of the quantum dot layer away from the anode, and performing a heating treatment to obtain a first sub-electron transport layer; An ethanol solution of Alq3 is coated on the surface of the first electron transport layer away from the anode, and heat-treated to obtain a second electron transport layer.
8. The method according to claim 7, characterized in that The preparation method of the ethylene glycol ether solution of ZnTiO3 comprises: Using ZnCl2 and TiCl4 as raw materials, ammonia water as a mineralizer, and deionized water as a medium in a reactor, ZnCl2, TiCl4 and ammonia water are reacted at 270-290 degrees in the reactor for 8h-10h; Then, the reaction product in the reactor is subjected to high temperature annealing treatment to obtain ZnTiO3; Finally, prepare ZnTiO3 ethylene glycol ether solution. Optionally, the temperature of the high temperature annealing treatment is 800-900°C.
9. The method according to claim 7 or 8, characterized in that: Further including: Coating a hole injection layer coating liquid on the surface of the anode and performing a heat treatment to obtain the hole injection layer; A hole transport layer coating liquid is coated on the surface of the hole injection layer away from the anode, and the surface is subjected to heat treatment to obtain the hole transport layer.
10. A display device, characterized in that: A quantum dot light-emitting device comprising any one of claims 1-6.
Citation Information
Patent Citations
Quantum dot electroluminescent device and display
CN108963087A